Hydration and plasticization effects of maltodextrin on the structure and cooking quality of extruded whole buckwheat noodles. (16th April 2022) - Xu, Xiang; Gao, Chengcheng; Xu, Jingwen; Meng, Linghan; Wang, Zhenjiong; Yang, Yuling; Shen, Xinchun; Tang, Xiaozhi
Graphical abstract: Highlights: Maltodextrin addition improved structure and quality of extruded buckwheat noodles. Hydrogen bonds formed between maltodextrin and buckwheat starch molecules. The plasticization effects of maltodextrin enhanced maximum Elongation of noodles. Cooking time decreased to 3.1 min due to the hydration effects of maltodextrin. Abstract: In order to improve the structure and cooking quality of extruded whole buckwheat noodles (EWBN), maltodextrin (MD), the homologous substances of starch, was added to buckwheat flour to prepare the EWBN. Hydrogen bonds formed between MD and buckwheat starch molecules and the crystallinity of EWBN decreased as determined by FT-IR and X-ray diffraction, which indicated plasticization effects of MD on buckwheat starch. The content of tightly bound water first increased and then decreased with the increasing amount of MD and the cooking time of EWBM decreased from 5.4 to 3.1 min due to the hydration effects of MD. The cooking loss first decreased and then increased, and showed a minimum value of 9.22% when adding 1 wt% of MD. For texture properties, the hardness, stickiness, chewiness and elongation at break of EWBN first increased and then decreased with the addition of MD, and all reached the maximum value at 3 wt% of MD. These findings showed the potential of adding MD, especially at the appropriate concentration, for improving structure and cooking quality of EWBN.